Study of steel‐WC interface produced by solid‐state capacitor discharge sinter‐welding. (12th February 2016) - Maizza, G.; Cagliero, R.; Iacobone, A.; Montanari, R.; Varone, A.; Mezzi, A.; Kaciulis, S.
Abstract : Multimaterial components are more suitable than monolithic materials to combine several mechanical and functional properties simultaneously. Bi‐layer components made of WC‐Co and steel can combine enhanced wear resistance and toughness, which are beneficial for a wide range of advanced tribo‐structural applications. In this study, a new solid‐state capacitor discharge sinter‐welding (CDSW) process has been used to achieve an AISI M2 steel/WC–12% Co joint starting from green compacts. The CDSW process allows very short processing times, which help to prevent the coarsening of steel grains or WC particles, as well as avoid WC decomposition and minimize microstructural defects. The morphological, chemical, and structural characteristics of the phases and interface have been investigated. The results demonstrate an intimate bonding of the two joining materials and a significant diffusion of substitutional elements up to 100–150 µm apart from the interface. Copyright © 2016 John Wiley & Sons, Ltd.